Propuesta de diseño de planta para la empresa Gusticos Light ubicada en el Municipio de Ciénaga, Magdalena. (2023)
In the present research work, whose objective is to propose a plant design for the Gusticos Light company located in Ciénaga Magdalena, a company dedicated to the production of Confectionery, the SWOT matrix was made to demonstrate different aspects of the company and an analysis of the situation. current to recognize the Causes-Effects; The design of the plant was carried out using the Guerchet and SLP method to determine the areas required in the design in order to increase the level of productivity, the CORELAP design program was used, which yielded the most appropriate design for the distribution. The design was already obtained, the total budget of the design proposal was made, recognizing the expenses generated by the adaptation of the place, the tools and utensils that are going to be used, finally, a Cost-Benefit analysis was carried out that modified us to guarantee the viability of the design proposal with x% (equis percentage).